PERILAKU GESER BALOK CASTELLATED BENTUK LUBANG SEGIEMPAT DENGAN TULANGAN DAN KOMPOSIT MORTAR - , DINA HELDITA, Prof. Ir. Iman Satyarno, ME, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Castellated steel beam is upgraded beam from IWF profile to have large inertia moment in order to obtain higher flexural capacity than standard IWF profile. One of the weaknesses of castellated steel is the inefficiency in continuous beam. Commonly, when positive moment is much lesser than the negative, the profile shape is constant. Thus, to cope with its weakness and to increase the shear and moment capacity of the castellated steel, it is required to add longitudinal reinforcement, shear reinforcement and the mortar composite. The objective of this study is to identify the shear behaviors in the castellated steel with reinforcement and mortar composite. The test was taken to two castellated steel beams: one non-composite castellated steel beam (BC) and one composite castellated steel beam (BK) in 277 mm height, 75 mm flange width, 7 mm flange thickness and 5 mm web thickness. The reinforcement used was 2D16 for longitudinal reinforcement and 2P8 (114-146) mm for shear reinforcement. Mortar was made in cement-sand weight composition of 1:1,5, with 0,4 fas and viscocerete-10 in 0,7% of the cement weight. The test method used the two point static load with average load increase of 5 kN. The test was stopped when minimum load decrease occurred in 20% of the ultimate load . Results indicated the increase of maximum load (Pmaks) for BC and BK specimens were 34 kN and 582 kN, respectively. The flexure occurred at the maximum load for BC and BK specimens were 75,31 mm and 6,95 mm, respectively. For BK, significant increase of load occurred after the specimen swelled and experience significant crack distribution. Based on the crack pattern, BC can be categorized as plastically joint collapsing and BK as shear collapse. In BK with hair crack damage, it occurred when the load was relatively low. The mortar damage on the outmost compressive fiber started to occur when approaching the maximum load. Spalling occurred when maximum load was achieved. Based on the test results, it can be concluded that the addition of reinforcement and mortar would increase the shear capacity and cope with the weakness of castellated steel beam itself.